Are native bees and Apis mellifera equally efficient pollinators of the rupestrian grassland daisy Aspilia jolyana (Asteraceae)? - Maruyama, Pietro K.; Nunes, Carlos E. P.; Vizentin-Bugoni, Jeferson; Gustafsson, Simone; Morellato, Leonor Patrícia Cerdeira [UNESP] (Soc Botanica Brasil, 2018)
Most angiosperms rely on animals for pollination, and insects, especially bees, are the most frequent pollinators. Many native Neotropical plants are frequently visited by the invasive honeybee (Apis mellifera), but its role in the pollination of these plants has been little investigated. We assessed the contribution of various floral visitors, including native bees and the honeybee, on the pollination of a generalist rupestrian grassland daisy, Aspilia jolyana (Asteraceae), in Serra do Cipo, Espinhaco Mountain Range, Brazil. We recorded floral visitors and measured the seed set resulting from one single visitation. We observed a total of 442 visits, mostly by bees, with Bombus pauloensis and Apis mellifera being the most common floral visitors. Other visitors included many other species of bees, flies, hummingbirds, wasps and butterflies. Pollinators significantly increased seed set in comparison to non-visited (bagged) capitula. Moreover, there was no difference among bee species/groups in their contribution to seed set. Thus, A. jolyana benefits from its generalized pollination strategy, and frequent bee visitors, including several native species and the invasive honeybee, are equally effective pollinators for this generalist daisy of rupestrian grasslands.
Keywords: bee pollination; Bombus pauloensis; generalization; honeybee; invasive species; pollination efficacy; Serra do Cipo; span style=color:red Bombus style=color:red pauloensis; style=color:red generalization; style=color:red Serra do Cipo